(untitled) (Revista ABRA, 2016)
This paper explores the possibility of Costa Rican schools teaching International Relations and the Ministry of Foreign Affairs to generate knowledge input that can be translated into external policy knowledge output in the Central American subsystem. Informants included program coordinators and professors from public and private universities and the Minister of Foreign Affairs. In order to implement an action in this area, the following should be taken into consideration: first consider environmental sustainability, improve relevance criteria of academic research processes, and improve the quality of applied research. In addition, it should be considered that Costa Rican schools that teach International Affairs do not have experience teaching Think Tanks.